The role of lyrics in music–exercise performance on perceived exertion - Ehsan Zareıan; Karen Baranı; Zahra Pooraghaeı (Türk Spor ve Egzersiz Dergisi)
The research aimed to examine the role of lyrics in music on perceived exertion of male and female students during physical activity (running on treadmill). For this purpose, 23 (11 males, 12 females) were selected randomly among volunteered students. The participants underwent physical activity under condition of lyrics music in the first session, same no-lyrics music in the second session and no music in the third session. The test duration was 5 minutes for all participants and their running intensity was in correspondence with 80% of their maximum heart rate. The recovery period between each session was 48 hrs. After each session, the participants specified their rated perceived exertion (RPE) by completing the Borg scale questionnaire. The results of ANOVA revealed that lyrics music had a significant effect on the participants' perceived exertion, but no-lyrics music had no effect on their perceived exertion. With regard to reduction of the perceived exertion rate during the use of lyrics music, it can be concluded that the presence of lyrics in music reduces the participants' perceived exertion and causes the activity time to seem shorter. It can be deduced that the presence of lyrics in music has a significant effect on the improvement of psychological conditions of athletes and their perceived exertion.